Evaluation of Pulse Rate, Oxygen Saturation, and Respiratory Effort after Different Types of Feeding Methods in Preterm Newborns - Dipen Vasudev Patel; Dharti Shah; Kunjal A. Kantharia; Mayur K. Shinde; Jaishree Ganjiwale; Kushal Shah; Somashekhar Marutirao Nimbalkar (International Journal of Pediatrics)
Background. During the initial days of hospitalization, preterm newborns are given combinations of breastfeeding, spoon/paladai feeding, and/or gavage feeding. Each method of feeding may have a different effect on vital parameters. Objective. To study changes in vital parameters in relation to different feeding methods and postmenstrual age (PMA) in preterm newborns. Study Design. This prospective observational study was carried out at a tertiary care neonatal unit. Participants. Physiologically stable preterm newborns with PMA less than 37 weeks on full enteral feeds were included in the study. Intervention. None. Outcomes. Respiratory rate (RR), pulse rate (PR), oxygen saturation (SPO2), nasal flaring, and lower chest indrawing were monitored before and up to 3 h after the breastfeeding/spoon (paladai) feeding/gavage feeding or their combinations. These vital parameters were assessed in relation to the feeding methods and PMA groups using ANOVA. Results. A total of 383 records were analyzed from 110 newborns. No infant developed chest indrawing or nasal flaring after any feeding method. During the 3 h period of monitoring, vital parameters changed significantly except in the gavage feeding group. The mean PR did not change, but the mean RR and SPO2 changed significantly at different PMA. Conclusion. Vital parameters changed after different types of feeding methods and at different PMA. A further multicentric prospective study is needed to understand the effect of different feeding methods and PMA on vital parameters.